Role of complement anaphylatoxin receptor in cervical cancer growth - Nur Aireena Affeza Muhamad Amran, 1993-; Fazrena Nadia Akhir, supervisor; Fakulti Biosains dan Kejuruteraan Perubatan (2016)
Project Paper (Sarjana Muda Sains (Biologi)) - Universiti Teknologi Malaysia, 2017